An Interview Survey: Knowledge on Chemical Hazards Among Chemistry Laboratory Staff at Secondary - Muhammad Rushdi, Abdul Rahman (Universiti Sains Malaysia, 2006)
The project aimed to evaluate the level of knowledge chemical and practice of chemical safety and also promote knowledge pertaining to hazardous chemical to staff working in the chemistry laboratory. Indirectly, the awareness of staff on the importance of chemical safety was also evaluated. The study was at chemistry laboratory of secondary schools in Kubang Kerian. There 5 schools in the Kubang Kerian district that have chemistry laboratory. A standard questionnaire was developed and utilized to obtain feedback from the laboratory staff. All the respondent willingly completed the questionnaire through verbal interview. These questionnaire includes question pertaining to classification of hazardous chemicals, ability to identify chemical hazards based on CPL ( Classification, Packaging and Labeling) Regulation 1997, storing of bulk chemicals, recognizing chemicals warning symbol, handling control measures, training, and to access MSDS ( Material Safety Data Sheets) and understanding of CPL ( Classification, Packaging and Labeling) Regulation 1997. The result indicated that all the respondents are unaware of MSDS and the need to obey CPL Regulation 1997. Specific training about handling and managing hazardous chemicals was less provided. While some general chemical control measure were not practiced, lack of personal protective equipment and administrative controls which means safety are not emphasized in the laboratory. This information can be used in increasing awareness about hazardous chemicals, and extent to the planning and prioritizing of educative and other preventive strategies, to minimize risks to health and safety arising from work with hazardous chemicals substances.